Enculturation in Formal Education: A Multi-Case Study of Local Cultural Preservation Practices in Gowa, South Sulawesi - Sulmi Sulmi; Najamuddin Najamuddin; Bahri Bahri; Bakhtiar Bakhtiar (Journal of Innovation and Research in Primary Education, 2026)
The sustainability of local cultural heritage in Indonesian secondary schools is increasingly threatened by globalization and the absence of systematic institutional frameworks for cultural preservation. Despite the strategic role of schools as agents of enculturation, empirical evidence on how different institutional contexts shape cultural preservation practices remains limited, particularly in culturally rich regions such as Gowa Regency, South Sulawesi. This study employed a qualitative multiple case study design across three secondary schools — SMA Negeri 1 Gowa, SMA Negeri 9 Gowa, and Pesantren Sultan Hasanuddin. Data were collected through semi-structured interviews, participatory observation, and documentary analysis involving 27 purposively selected participants. Analysis followed the Miles et al. (2014) interactive model, with source and method triangulation applied to ensure trustworthiness. Three institutional preservation models were identified: the structural model (policy-embedded), the ceremonial model (initiative-dependent), and the holistic model (tradition-immersive). Sustainability was highest where programs were formally institutionalized or deeply embedded in boarding-school traditions. Findings confirm that effective enculturation operates through the convergence of transformational leadership, culturally responsive pedagogy, hidden curriculum, and school-community collaboration. An unexpected synergy between Islamic and Bugis-Makassar values at PSH revealed the underexplored potential of faith-based schools as sites of cultural resilience. Local cultural preservation in schools demands systemic institutionalization beyond ceremonial activities. The proposed typology offers a transferable conceptual framework for policy and further comparative research.